Zero and Minimal Fluoroscopic Approaches During Ablation of Supraventricular Tachycardias A Systematic Review and Meta-Analysis - Debreceni Dorottya (FRONTIERS IN CARDIOVASCULAR MEDICINE, 2022)
Catheter ablations for cardiac arrhythmias are conventionally performed under fluoroscopic guidance. To guide these procedures, zero/minimal fluoroscopy (Z/MF) approaches have become available, using three-dimensional electroanatomical mapping systems. Our aim was to conduct a meta-analysis comparing these two different methods for the treatment of paroxysmal supraventricular tachycardia (SVT).Electronic databases were searched and systematically reviewed for studies comparing procedural parameters and outcomes of conventional, fluoroscopy-guided vs. Z/MF approaches in patients undergoing electrophysiology (EP) procedures for SVTs. The random-effects model was used to derive mean difference (MD) and risk ratios (RRs) with 95% confidence interval (CI).Twenty-four studies involving 9,074 patients met our inclusion criteria. There was no difference between the groups in terms of acute success rate (RR = 1.00, 95% CI, 0.99-1.01; p = 0.97) and long-term success rate (RR: 1.01, 95% CI, 1.00-1.03; p = 0.13). Compared to the conventional method, zero-and-minimal fluoroscopy (Z/MF) ablation significantly reduced fluoroscopic time [MD: -1.58 min (95% CI, -2.21 to -0.96 min; p < 0.01)] and ablation time [MD: -25.23 s (95% CI: -42.04 to -8.43 s; p < 0.01)]. No difference could be detected between the two groups in terms of the procedure time [MD: 3.06 min (95% CI: -0.97 to 7.08; p = 0.14)] and the number of ablation applications [MD: 0.13 (95% CI: -0.86 to 1.11; p = 0.80)]. The complication rate was 1.59% in the entire study population and did not differ among the groups (RR: 0.68, 95% CI: 0.45-1.05; p = 0.08).The Z/MF approach for the catheter ablation of SVTs is a feasible method that reduces radiation exposure and ablation time without compromising the acute and long-term success or complication rates.